Quantitative high-resolution observations of soil water dynamics in a complicated architecture with time-lapse ground-penetrating Radar - Klenk, Patrick; Jaumann, Stefan; Roth, Kurt (Hydrology and earth system sciences discussions, 2014)
High-resolution time-lapse Ground-Penetrating Radar (GPR) observations - of advancing and retreating water tables can yield a wealth of - information about near-surface water content dynamics. In this study, we - present and analyze a series of imbibition, drainage and infiltration - experiments which have been carried out at our artificial ASSESS test - site and observed with surface based GPR. The test site features a - complicated but known subsurface architecture constructed with three - different kinds of sand. It allows studying soil water dynamics with GPR - under a wide range of different conditions. Here, we assess in - particular (i) the accurate determination of soil water dynamics - averaged over the whole vertical extent by evaluating the bottom - reflection and (ii) the feasibility of monitoring the dynamic shape of - the capillary fringe reflection. The phenomenology of the GPR response - of a dynamically changing capillary fringe is developed from a soil - physical point of view. We then explain experimentally observed - phenomena based on numerical simulations of both the water content - dynamics and the expected GPR response.